FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERLANJUTAN MODEL PENGEMBANGAN AGROWISATA BERBASIS KEARIFAN LOKAL (Studi Kasus di Desa Karangtengah Kecamatan Imogiri Kabupaten Bantul Daerah Istimewa Yogyakarta) - Sriyadi, Sriyadi; Akhmadi, Heri; Yekti, Ananti (Agridevina : Berkala Ilmiah Agribisnis, 2021)
To anticipate and develop rural areas, the government is currently promoting rural social and economic development, including the development of rural agribusiness and rural agro-tourism programs. This study aims to determine the factors that influence the sustainability of the agro-tourism development model based on local wisdom. The research was conducted by surveying interviews with farmers and related parties as well as field observations. Factors that have a relationship with the sustainability of agro-tourism development based on local wisdom are skills, amount of finance, access to capital sources and availability of facilities. It is recommended that stakeholders need to improve skills, ease of access to sources of capital from local governments and the need for additional agro-tourism facilities DOI : https://doi.org/10.33005/adv.v10i2.2746.